Financial Literacy as a Buffer Against Behavioral Biases in Students’ Investment Decisions - WARDHANA, BAGUS DWI ARTHA (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
Student participation as young investors in the Indonesian capital market has increased rapidly in recent years. This phenomenon has been triggered by developments in financial technology and ease of access to investment instruments. However, this increase in participation isn't always matched by rational decision-making skills, because students are prone to various behavioral biases such as overconfidence, representativeness, fear of missing out (FOMO), disposition effect, and anchoring. This study explores the role of financial literacy in mitigating behavioral biases among economics students in investment decision-making. Using a descriptive qualitative approach, this study involved Economics students who had investment experience at Malang State University. Data was collected through semi-structured in-depth interviews and analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that financial literacy plays an important role in reducing the impact of behavioral biases, particularly in the areas of risk management, portfolio diversification, and fundamental analysis-based decision making. However, financial literacy cannot completely eliminate the influence of strong emotional and social factors in the investment process. This study highlights the importance of financial literacy as a buffer against behavioral biases, while recommending the need for more practical and contextual financial literacy programs in higher education institutions. In addition, the findings suggest the need to integrate financial literacy into curriculum design, encourage collaboration between universities and financial regulators, and consider broader policy implications to strengthen students’ capacity for rational investment decision making